Angat Dalag: The viability of mudfish cultivation in Pampanga - Phoebe Stacey M. Almario, Alexandre Miguel P. Avila, Jester Paul D. Cortes, Ralph Adriell M. Escudero, Caezar Adrian B. Mosquito, Rufino D. Pamaran III, Gabriel Leoj B. Rosales, Pranz Edrian P. Timan 4 0 16; 5
Abstract As the Philippines' fishing industry is in the downtrend, output resulted in a lot of importation in the past few years (Viron, 2019). In the year of 2022, the Philippines' fish supply was in shortage wherein the country was obligated to have an import of 60,000 metric tons of fish to fill the demand of the country (Lagare, 2022). As these several problems arose, the researchers decided to make a business which wanted to tackle the problem of fish supply in the market. In line with this, the researchers focus on raising Dalag or Mudfish that will be conducted in acquiring a fish farm in the vicinity of Barangay Camba, Arayat, Pampanga, Philippines. This will provide an additional source of supply of fish in the market. In addition, the team was motivated to integrate its product called Dalag in the fish wet markets in the City of Manila to have alternative fish products in the industry. Moreover, the team sees that introducing the benefits and uses of Dalag will make a good recognition that can benefit the country in terms of fish supply. Keywords: Fishing Industry, Shortage, Importation, Fish Supply, Dalag or Mudfish, Fish Farm, Wet Markets
Feasibility Study: (BSBA major in Business Economics) - Pamantasan ng Lungsod ng Maynila, 2023
Keywords: 2 -- 0; 6; 20; 20; 2